Analysis method and empirical research on economic benefit of large‐scale consumptive power grid investment. Issue 13 (4th December 2017) - Ge, Yi; He, Yue; Hu, Xiaoyan; Sun, Wentao; Zhang, Wenjia; Huang, Junhui
Abstract : Inter‐area transmission network planning task is on the basis of existing load and power planning, to determine the new inter‐area tie‐line location and capacity and in order to achieve the power supply capability needed in the planning period, under the precondition of satisfying the various technical indicators of the end system with lowest cost. Through the life‐cycle cost method, this study evaluates the investment benefit of consumptive UHV external power supply construction by receiving end system of power grid. Empirical study has been carried out using one of the Jiangsu power grid planning schemes of 2020. Economy benefit of investment has been analysed through the sequential operating simulation result of Jinbei–Nanjing UHVDC scheme. Economic balance operating position of Jinbei UHVDC can be acquired, which provides an important guiding role for the overall efficiency of economic operation of large‐scale interconnected power grid.